2016
DOI: 10.1111/hae.12916
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between FIX genotype and pharmacokinetics of Nonacog alpha according to a multicentre Italian study

Abstract: Introduction: Pharmacokinetic (PK) studies on recombinant FIX concentrate, Nonacog alpha, were conducted with different sampling time designs which gave rise to not complete and homogenous outcomes. In addition, patient's FIX genotype/PK relationship has never been investigated. Aim: Investigate how different sampling times may affect PK parameters and try to find a FIX genotype/PK relationship. Patients and Methods: A cohort pharmacokinetic, Nonacog Alpha single-dose, open-label, non-comparative study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…The limited PK data available showed trough levels of <0.01-0.12 IU mL À1 , 5 to 7-days post-infusion in eight patients; in keeping with the longer terminal rFIX half-life recently reported [2,5]. Morfini observed long half-lives of 33.8-57.5 h in patients with missense and nonsense mutations, but very short half-lives of 5.02 and 9.69 h in two patients with FIX deletions [5]. Although the genotype was known for 17/20 of our patients, no obvious link could be shown between genotype, weekly dosage or ABR.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The limited PK data available showed trough levels of <0.01-0.12 IU mL À1 , 5 to 7-days post-infusion in eight patients; in keeping with the longer terminal rFIX half-life recently reported [2,5]. Morfini observed long half-lives of 33.8-57.5 h in patients with missense and nonsense mutations, but very short half-lives of 5.02 and 9.69 h in two patients with FIX deletions [5]. Although the genotype was known for 17/20 of our patients, no obvious link could be shown between genotype, weekly dosage or ABR.…”
supporting
confidence: 75%
“…Although EHL-IX has a longer terminal half-life than rFIX, this is not consistently reflected in an improved clinical outcome and the annualized bleedrates (ABR) reported for standard and EHL-products are surprisingly similar [2][3][4]. These studies have also demonstrated a median terminal half-life for rFIX of 35-hmuch longer than previously reported [2,5]. These observations suggest that OWP with standard rFIX may have wider utility than previously recognized.…”
mentioning
confidence: 68%
“…No significant differences in elimination HL are recognized between plasma‐derived and recombinant FVIII concentrate bioequivalence studies, but small differences between their alpha‐HL distributions exist . Although FVIII genotype does not affect FVIII concentrate PK, FIX genotype may interfere with nonacog alpha PK, because FIX mutations may produce non‐active or truncated proteins that compete with infused concentrate for binding to collagen type IV or filling the extravascular space . Blood group O and low VWF concentration are well‐known covariates interfering with FVIII HL, but not protein C and LRP1; other plasma proteins or cell receptor polymorphisms are under investigation (Morfini and Bernardi, unpublished data).…”
Section: Pharmacokinetic Considerationsmentioning
confidence: 99%
“…Only in phase 3 head-to-head study of rFIX-Fc, the PK of pdFIX and rFIX have been prolonged up to 72 and 96 h [74]. It is easy to understand how prolonged sample timing causes a larger AUC, a smaller Cl, and a longer HL, as shown by a recent Italian multicentre PK study [75]. Similar findings have been observed in a PK study of nonacog alfa conducted in China [76].…”
Section: Dna-recombinant Clotting Factor Concentrates and Their Phmentioning
confidence: 65%